The Influence of Halal Labels and Product Quality on Food Product Consumption Decisions with Trust as an Intervening Variable (Case Study of Tembung Champion Meatballs) - Putri Winanda; Nur Ahmadi Bi Rahmani; Atika Atika (Indonesian Journal of Islamic Economics and Finance, 2026)
This study aims to analyze the influence of halal labels and product quality on food product consumption, with consumer trust serving as an intervening variable, at Bakso Urat Juara Tembung. A quantitative approach was employed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The sample consisted of 100 Muslim consumers who had previously consumed the product. Data were collected through a Likert-scale questionnaire and analyzed using SmartPLS. The findings indicate that halal labels and product quality do not have a significant direct effect on food product consumption. However, both variables significantly influence consumer trust, which in turn has a significant positive effect on consumption behavior. Trust also mediates the relationship between halal labels, product quality, and food product consumption. The R-Square value for Trust was 0.905 (adjusted R² = 0.903), indicating that 90.5% of consumer trust is explained by halal labels and product quality. The R-Square value for Food Product Consumption was 0.801 (adjusted R² = 0.795), showing strong explanatory power. Importantly, trust functions as a full mediator. The direct effects of Halal Label (coefficient = -0.109; p = 0.434) and Product Quality (coefficient = 0.362; p = 0.069) on consumption were insignificant, while their indirect effects through Trust were significant (Halal Label: coefficient = 0.236; p = 0.016; Product Quality: coefficient = 0.395; p = 0.007). These results suggest that consumer trust serves as the key psychological mechanism linking sellers’ claims and product attributes to actual consumption decisions. Therefore, obtaining official halal certification and implementing transparent business practices are recommended to strengthen trust and encourage sustainable consumption.